(2R,3R)-2-[(4-Chlorophenyl)hydroxymethyl]cyclopentanone - Deng, Dongsheng (International Union of Crystallography, 2008)
The title compound, C(12)H(13)ClO(2), was prepared by the direct asymmetric intermolecular aldol reaction of cyclopentanone and 4-chlorobenzaldehyde catalysed by l-tryptophan in water. The absolute molecular structure was determined to be a racemic twin with 91% (2R,3R) isomer and 9% of the (2S,3S) form. In the crystal structure, the molecules are connected into a one-dimensional chain along the a axis through the formation of intermolecular O—H⋯O hydrogen bonds. Further, non-conventional C—H⋯O and C—H⋯π contacts are observed in the structure, which consolidate the crystal packing.